Speak, Memory: Dignāga, Consciousness, and Awareness. - Silins, Nicholas (Australasian Journal of Philosophy, 2026)
When someone is in a conscious state, must they be aware of it? The Buddhist philosopher Dignāga offers a brilliant route to answering this question by leveraging the role awareness might play as a constraint on memory. I begin by clarifying his strategy and what conclusions it might be used to establish, and then turn to explain why it fails. The first main problem is that, contrary to his contemporary defenders, there is no good way to use it to reach a conclusion about all conscious states. The second main problem is that the proposed awareness constraint on memory is highly problematic, in tension both with ancient objections as well as current psychology.